Kewenangan Kelurahan Pasca Undang-Undang Nomor 9 Tahun 2015 Tentang Pemerintahan Daerah Kaitannya Dengan Otonomi Daerah - okparizan, okparizan (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2016)
Decentralization can be defined as the delivery of affairs by the central government to the regions based on the principle of autonomy. The Village can be interpreted as a form of